Synthesis of a novel zirconium-based adsorbent (ZBA) and the elucidation of adsorption capability of arsenic using ZBA, zirconium oxide, and zirconium hydroxide - Fumihiko Ogata; Noriaki Nagai; Yugo Uematsu; Hitoka Ito; Chalermpong Saenjum; Naohito Kawasaki (Results in Chemistry)
A novel zirconium-based adsorbent (ZBA) was prepared and characterized. The results were compared to those of zirconium oxide (ZrO2) and zirconium hydroxide (Zr(OH)4). Moreover, the arsenic adsorption capacity of the ZBA was demonstrated. The physicochemical properties of the ZBA were similar to those of Zr(OH)4, and the ZBA was confirmed to be zirconium oxyhydroxide (ZrO(OH)2). The batch test results indicated that the adsorption of arsenic ions on ZBA or Zr(OH)4 (Maximum adsorption capacity: approximately 70 mg/g) was higher than that on ZrO2 (Maximum adsorption capacity: approximately 10 mg/g). The adsorption isotherms indicated arsenic ions were presented on the surface of ZBA and Zr(OH)4. The Freundlich model (r = 0.953–0.997) and the Langmuir model (r = 0.961–0.994) showed a good fit to the experimental results. In addition, the findings from the binding energy and elemental distribution analysis confirmed that arsenic ions were adsorbed on the ZBA surface. The adsorption kinetic data aligned more closely with the pseudo-second-order model (r = 0.992–0.996) compared to the pseudo-first-order model (r = 0.709–0.836), except for ZrO2. The optimal pH conditions for the removal of arsenic ions on the ZBA and Zr(OH)4 under the proposed experimental conditions were pH = 6–10. Moreover, the amounts of arsenic ions adsorbed on the ZBA or Zr(OH)4 in binary solution systems were slightly lower than those in single solution systems. However, ZBA maintained high arsenic adsorption capability in binary solution systems. Finally, the adsorbed arsenic ions on ZBA or Zr(OH)4 were easily desorbed using a desorption solution, such as hydrochloric acid or sodium hydroxide solution, and the desorption efficiency increased with the concentration of the desorption solution. Overall, the excellent arsenic-ion removal efficiency of the proposed ZBA makes it a promising material for the treatment of arsenic-ion-polluted wastewater.